Quantifying change of direction movement demands in professional tennis matchplay: an analysis from the Australian Open Grand Slam - Giles, B.; Peeling, P.; Reid, M. (The Journal of Strength and Conditioning Research, 2024)
Change of direction (COD) contributes significantly to the movement repertoire of professional tennis players, yet the time-motion and degree demands of these changes are poorly understood. This study examines the velocity, acceleration, and angular displacement profiles of COD movements in modern professional tennis. One hundred eighty-two singles matches of Hawk-Eye player tracking data collected from the Australian Open Grand Slam were used for analysis. A novel COD classification algorithm was used to identify >120,000 medium and high-intensity CODs for analysis. Descriptive characteristics of the COD performance were calculated using player coordinate and time variables. Sex comparisons were analyzed using 2 mixed-effects models assessed for differences via likelihood ratios. Players performed 1.6 CODs per point. Both sexes executed, on average, 1.3-1.4 shots and covered 4.8 m per COD, with men performing changes every 2.7 seconds and women every 3.1 seconds. Medium-intensity COD comprised 88-94% of all identified changes. Approximately 2 in 3 CODs involved a degree of change >105°, whereas cutting maneuvers (<45°) were most commonly high-intensity COD. This study is the first to quantify the COD characteristics of professional tennis matchplay. Both sexes performed the same average number of CODs per point, however, men executed high-intensity changes twice as frequently as women, at an average of 1 every 5 points. These novel findings will help to improve the specificity of training interventions in elite tennis conditioning.